2018
DOI: 10.3390/geosciences8120452
|View full text |Cite
|
Sign up to set email alerts
|

Survey Tool for Rapid Assessment of Socio-Economic Vulnerability of Fishing Communities in Vietnam to Climate Change

Abstract: Climate change will likely affect the effectiveness of future management of coastal ecosystems, impacting communities that reside within the coastal area. In order to formulate appropriate adaptation counter-measures it is important to understand the actual vulnerability of the communities that depend on these ecosystems. The present research proposes a tool for assessing the vulnerability of coastal communities to climate change by combining survey results with secondary and observed data available from natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The present mini review highlights the large variety of frameworks and approaches-resulting from different combinations of elements, dimensions, and spatial scales included in the analyses-that can be used to develop climaterelated vulnerability and risk assessments. Different methods exist, for example, to assess the vulnerability to climate change of a fishing community, a marine renewable energy facility, or a marine protected area, making it extremely difficult and subjective to decide on the methodologies and indicators to use (Brugère and Young, 2015;Monnereau et al, 2017;Avelino et al, 2018;Wabnitz et al, 2018;Zhang et al, 2018). In effect, given the myriad of fields (e.g., environmental sciences, economics, health) that use such assessments, together with the range of possible interpretations and meanings (e.g., Bennett et al, 2016;Weißhuhn et al, 2018;Comte et al, 2019), and variety of objectives and models to be used (Patwardhan, 2006), it is extremely challenging to find a one-size approach to fit all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present mini review highlights the large variety of frameworks and approaches-resulting from different combinations of elements, dimensions, and spatial scales included in the analyses-that can be used to develop climaterelated vulnerability and risk assessments. Different methods exist, for example, to assess the vulnerability to climate change of a fishing community, a marine renewable energy facility, or a marine protected area, making it extremely difficult and subjective to decide on the methodologies and indicators to use (Brugère and Young, 2015;Monnereau et al, 2017;Avelino et al, 2018;Wabnitz et al, 2018;Zhang et al, 2018). In effect, given the myriad of fields (e.g., environmental sciences, economics, health) that use such assessments, together with the range of possible interpretations and meanings (e.g., Bennett et al, 2016;Weißhuhn et al, 2018;Comte et al, 2019), and variety of objectives and models to be used (Patwardhan, 2006), it is extremely challenging to find a one-size approach to fit all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The concepts of vulnerability and risk have long been applied in a variety of contexts, including the assessment of anthropogenic and natural hazards to human, health, nature, or economic growth (Adger, 2006;Bernard and Ostländer, 2008;Moreno and Becken, 2009;Salim et al, 2014). More recently, vulnerability and risk analyses have been increasingly used to address climate change effects on the ocean (Brugère and Young, 2015;Avelino et al, 2018;Wabnitz et al, 2018;Comte et al, 2019). However, finding definitions of vulnerability and risk that are consistently applied and accepted is not straightforward, due to the myriad of existing designations and interpretations, and the variety of fields in which they are applied (e.g., environmental, social, economic) (Brugère and Young, 2015;Bennett et al, 2016;Weis et al, 2016;Weißhuhn et al, 2018;Comte et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Schomaker's (1997) SMART indicator framework: specific, measurable, achievable, relevant and time‐bound, is used in this study to select indicators to identify common but differentiated responsibilities. Initially, a pool of 336 socio‐economic indicators from 10 studies were identified to be used in the analysis (Accadia & Spagnolo, 2006; Avelino et al, 2018; Boyd & Charles, 2006; FAO, 2017a, 2017b; Kruse, 2012; Ãœnal & Franquesa, 2010; Wabnitz et al, 2018) (Figure 1). Further information on selected indicators and references for the data used for each indicator are included in the Supplementary Information.…”
Section: Methodological Approach: Indicators and Differentiated Respo...mentioning
confidence: 99%
“…For example, fewer than half of health-oriented VAAs internationally have estimated the future health impacts of climate change; that limitation reflects a common lack of data and analysis regarding relationships between climate drivers and health outcomes on which to build predictive models [66]. Other socially oriented VAAs have focused on vulnerability to widely predicted climatic impacts, particularly for low-lying coastal regions, such as increases in temperature, increased risk of intense storms and flooding, and sea-level rise [67][68][69].…”
Section: Temporal Referencesmentioning
confidence: 99%